Pencatatan Perkawinan dalam Teks Perundang-Undangan Perkawinan di Beberapa Negara Islam Perspektif Ushul Fikih - Supani, Supani (Al-Manahij: Jurnal Kajian Hukum Islam, 2011)
The provisions on marriage registration law are not explicitly stated by the texts of the Qur'an and Sunnah, albeit marriage is a legal event, creating rights and obligations of the parties. The fulfillment of these rights and obligations can be well enforced if an orderly marriage administration is in place, namely by registering the marriage to the competent institutions of marriage, evidenced by a marriage certificate (authentic evidence). Since the texts do not provide the laws, its explanation is also not found in conventional fiqh. Marriage laws in several Islamic countries also provide non-uniform provisions in terms of technical details, although the majority requires marriage registration. The legal importance of marriage registration can be strengthened by several methods of istinbath (usul fiqh), inter alia, the methods of qiyas, sadd al-z'ah, and al-maslahat al-mursalah. respectively.